Hematologic and serum biochemistry reference intervals using defined ASCVP methodology for laboratory natal multimammate mice (Mastomys natalensis). (October 2021) - Smith, Brian J; Hanley, Patrick W; Maiga, Ousmane; Culbert, Maarit N; Woods, Marissa J; Cordova, Kathleen; Clancy, Chad; Safronetz, David; Feldmann, Heinrich; Rosenke, Kyle; Tang-Huau, Tsing-Lee
Complete blood count, serum chemistry values, and biological reference intervals were compared between two age groups (34–49 and 84–120 days old) of healthy male and female laboratory raised natal multimammate mice ( Mastomys natalensis ). Blood was collected via cardiocentesis under isoflurane anesthesia. Data sets of machine automated complete blood counts and clinical chemistries were analyzed. Significant differences between sex and age groups of the data sets were defined. The baseline hematologic and serum biochemistry values described here can improve interpretation of laboratory research using natal multimammate mice.